Critical period of weed control in aerobic rice system - Arul Sebastian Micheal, Jaya Suria; Juraimi, Abdul Shukor; Selamat, Ahmad; Man, Azmi; Anwar, Md. Parvez; Uddin, Md. Kamal (Southern Cross Publishing, 2013)
To determine the critical period of weed control in an aerobic rice system, field trials were conducted using a quantitative series of treatments comprising of two treatments (a) weed interference (b) weed free period. The critical period was determined using Logistic and Gompertz equations. Yield of MRQ74 rice in an aerobic system would be severely impaired if weeds are not removed from 17 - 53 days after sowing (DAS). An acceptable yield loss of 5% is acceptable if weeds were controlled from 11 DAS to 74 DAS. Weeds compete significantly with AERON001 rice from 13 to 75 DAS for an acceptable 5% yield loss and 29 to 40 DAS for a 10% yield loss.